Context matters during pick-and-place in VR: Impact on search and transport phases - Lukashova-Sanz, Olga; Agarwala, Rajat; Wahl, Siegfried (Frontiers in Psychology, 2022)
When considering external assistive systems for people with motor impairments, gaze has been shown to be a powerful tool as it is anticipatory to motor actions and is promising for understanding the intentions of an individual even before the action. Up until now, the vast majority of studies investigating the coordinated eye and hand movement in a grasping task focused on single objects manipulation without placing them in a meaningful scene. Very little is known about the impact of the scene context on how we manipulate objects in an interactive task. In the present study, it was investigated how the scene context affects human object manipulation in a pick-and-place task in a realistic scenario implemented in VR. During the experiment, participants were instructed to find the target object in a room, pick it up, and transport it to a predefined final location. Thereafter, the impact of the scene context on different stages of the task was examined using head and hand movement, as well as eye tracking. As the main result, the scene context had a significant effect on the search and transport phases, but not on the reach phase of the task. The present work provides insights into the development of potential supporting intention predicting systems, revealing the dynamics of the pick-and-place task behavior once it is realized in a realistic context-rich scenario.